Iron, Iodine and Vitamin A in the Middle East; A Systematic Review of Deficiency and Food Fortification - P Mirmiran; M Golzarand; L Serra-Majem; F Azizi (Tehran University of Medical Sciences, 2012)
Background: Micronutrient deficiency is one of the major public health problems in the Middle East affecting economic, political and social development of countries. The three commonest micronutrient deficiencies belong to iron, iodine and vitamin A.  Methods: we conducted a systematic review of published English articles in the Middle East countries using databases from PubMed, World Health Organization and Food and Agriculture Organization from 1985 onward. A total of 6050 articles were identified and after evaluation based on eligibility criteria, 81 articles included in this systematic review. Results: Despite implementation of flour fortification other control strategies, the prevalence of iron deficiency is moderate to severe in the Middle Eastern countries, because of ineffective iron fortification program, food interaction and hemoglobin application as anemia indictors in these countries. Mild to severe iodine deficiency disorders exist in many countries of the Middle East, due to lack of effective iodine supplementation program. The prevalence of vitamin A deficiency is mild to severe and there is lack of vitamin A fortification program in many countries in this region. Conclusion: Despite unharmonized efforts to control malnutrition of micronutrients, iron, iodine and vitamin A deficiencies are still exist in some countries of the Middle East. Effective, well controlled and harmonized programs for elimination of micronutrient deficiencies need to be initiated for governments and supported by international organizations in this region.